Selective Feticide of The Aneuploid Fetus in a Twin Pregnancy: A Case Reports - Sinan Beksaç; Tülay Özlü; Sevim Balcı; Mehmet Alikaşifoğlu; Nur Çakar (Medical Network, 2006)
An obstetric ultrasound of a 38 years old woman with a dichorionic diamniotic twin pregnancy showed an increased nuchal translucency and absent nasal bone in one of the fetuses suggesting us an increased risk f or Down Sy ndrome (DS). This fetus was detected to hav e trisomy 21 (47, XX+21) by investigation of the amniocentesis material and was selectively undergone feticide process at 20 weeks of gestation. The other f etus (46, XX) was successf ully delivered at 36 weeks without any complications.